REDESIGNING JOB DESCRIPTION AND JOB SPECIFICATION OF DIKLAT DEPARTMENT IN PT TRANS INDONESIA FOR INCREASING STAFF AND SUPERVISOR PERFORMANCES FINAL PROJECT - Maryati, Titi; Putranto, Nur Arief Rahmatyah (Journal of Business and Management, 2017)
Abstract. The transportation industry in Indonesia is the most important industry. It is because Indonesia is the largest archipelago country in the world. Therefore, the transportation industry needs to be maintained and developed. One of the ways is through PT Trans Indonesia which engaged in the transportation industry. However, based on preliminary study, PT Trans Indonesia is facing problems at staffs and supervisors level in Diklat Department. Where Diklat Department has 1 manager position, 3 supervisor positions, and 4 staff positions. The symptom in Diklat Department can be seen from main responsibility that can not be fully handled, unfair compensation, ineffectiveness and inefficient job description's presentation, and less maximize the opportunity to fulfill job holder's job. After done Problem Tree Analysis was known that the root of the symptom lies in the need for restructuring job analysis to obtain an updates job description and job specifications. Therefore, the purpose of this study is to improve job descriptions and job specifications at the staff and supervisor level. Restructuring is done by doing qualitative approach that includes of questionnaires and interviews. In analyzing the need for restructuring, researchers also use scondary data. The result of restructuring describes the change of content and format on job description and job specification. The amendment is based on adjustments to the needs and circumstances for addressing fairness compensation, less informative job description, and dealing with the number of employees who reduced. So, this research can achieve the existing problems to improve employee performance, especially for staff and supervisor in Diklat Department in PT Trans Indonesia.Keywords:Â  Job Analysis, Job Description, Job Specification